Perceptions on intercultural communication training : academic and practical implications - Sette, Lucrezia (2020)
This thesis focuses on intercultural training. Specifically, the study will analyze some trainings organized for companies’ employees sent abroad for international assignments. The aim of this study is to find out different perceptions of the trainer and trainees on intercultural training. Traditional and critical scholars’ points of view will be also analysed and compared in order to elaborate suggestions for future developments. Moreover, the thesis will consider possible differences between the clients' expectations and the actual results of the training. Accordingly, the gata gathering will be conducted firstly through a survey addressed to trainees before the training and an interview with the trainer. Subsequently, trainees will be interviewed on their perceived outcomes of the training. The purpose of this research is to elaborate trainees’ feedback on the training and compare it to the trainer’s perspective in order to find potential problematic aspects of intercultural training. The analysis of these data will allow the thesis to make suggestions on how to develop the trainings. Also, intercultural encounters are becoming part of every-day life and an important aspect of international companies. Thus, also intercultural training is becoming a very common type of business and a much requested service. This phenomenon needs to be studied in order to effectively help expatriates and their families overcome the fear of "diversity", avoiding stereotypes and understanding inequalities. In this way, it is possible to help expats feeling satisfied with their working and private life, even if far away from home.